PENAMBAHAN SILASE JEROAN IKAN PATIN TERHADAP PERTUMBUHAN DAN KELANGSUNGAN HIDUP IKAN LELE (Clarias sp.) - Ida Ratnasari; Maryani Maryani; Nursiah Nursiah (Jurnal Akuakultur Sungai dan Danau, 2020)
Meeting the needs of feed today is experiencing a difficult time due to the high price of feed raw materials, especially fish meal, so that the impact on the price of the ration. Depending on the main source of protein in fish meal will certainly cause the availability of fish meal to be increasingly limited. Therefore an alternative source of protein is needed to reduce the use of fish meal in feed. Utilization of fishery waste into feed material can provide important significance for fisheries production, one of which allows it to be used as an alternative feed material is catfish processing waste on catfish viscera. This study aims to determine the effectiveness of catfish viscera in the manufacture of feed ration so as to produce growth and survival of catfish (Clarias sp.). The experimental design used was a Completely Randomized Design  with 3 treatments and 3 replications with A treatment (25% fish meal + 75% catfish viscera silage), B (50% fish flour + 50% catfish viscera silage), and C (75% fish meal + 25% catfish viscera silage). The results of the study conducted, showed the highest relative growth velocity value (%) of test fish in treatment C (222.63%) compared to treatments A (120.35%) and B (164.72%), the value of the feed conversion ratio (RKP) in treatment C obtained results which is relatively low with a value of 1.09 compared to other treatments that is 1.74 in treatment and treatment B with a value of 1.38. There was no significant effect on the addition of catfish viscera to the feed on the survival of catfish, so that there were no significant differences between treatments. Water quality in this study still supports the growth of catfish seedlings that are maintained.